Comorbidity and lifestyle, reproductive factors, and environmental exposures associated with rheumatoid arthritis. Issue 10 (1st October 2001) - Olsson, Å Reckner; Skogh, T; Wingren, G
Abstract : OBJECTIVE: To evaluate the influence of lifestyle, reproduction, and some external factors on the development of rheumatoid arthritis (RA) and to describe its comorbidity. METHODS: Cases were identified retrospectively from 1980 to 1995 at the University Hospital in Linköping, Sweden. The study comprised 422 cases and 859 randomly selected population referents. Data on possible aetiological factors and comorbidity were collected by postal questionnaire. RESULTS: The response rates were 67% among cases and 59% among referents. A decrease in the occurrence of atopic allergy was seen in the cases (odds ratio (OR) 0.6, 95% confidence interval (CI) 0.4 to 1.0). There was a positive association between RA and insulin treatment (OR 10.2, 95% CI 1.7 to 60.8) in women, and women with a short fertile period had an increased risk of RA (OR 2.5, 95% CI 1.1 to 5.4). Current and previous smoking were associated with increased risks for RA in both sexes, and in men a dose-response relationship was found with number of tobacco pack years (p for trend <0.005). The risk for RA decreased with increasing level of education in both men and women. Increased risks were seen in men born into households with private wells (OR 2.8, 95% CI 1.5 to 5.2), residentially exposed to mould (OR 4.6, 95% CI 1.1 to 20.2), or exposed to farm animals (OR 3.3, 95% CI 0.7 to 16.6). In women there were positive associations between RA and reporting a previous joint injury (OR 2.5, 95% CI 1.0 to 6.6) and prolonged exposure to hair dyes (OR 1.9, 95% CI 0.8 to 4.5). CONCLUSIONS: RA, a disease with features of T helper 1 (Th1) dominated immune response, was inversely associated with atopic allergy, a Th2 dominated condition, while there were indications of a strong positive association with Th1 related diabetes mellitus. The results support a causal relationship between smoking and RA. The level of education was inversely associated with RA, while there was a positive association between RA and certain residential factors in men and a short fertile period in women.